2020
DOI: 10.1016/j.jclinepi.2020.06.004
|View full text |Cite
|
Sign up to set email alerts
|

A framework for identifying and mitigating the equity harms of COVID-19 policy interventions

Abstract: Background: Coronavirus disease 2019 (COVID-19) is a global pandemic. Governments have implemented combinations of ''lockdown'' measures of various stringencies, including school and workplace closures, cancellations of public events, and restrictions on internal and external movements. These policy interventions are an attempt to shield high-risk individuals and to prevent overwhelming countries' healthcare systems, or, colloquially, ''flatten the curve.'' However, these policy interventions may come with phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
157
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 144 publications
(163 citation statements)
references
References 76 publications
3
157
0
3
Order By: Relevance
“…From all these studies, only one has collected original data involving 1478 adults [ 26 ]. The rest of the studies were comments [ 27 ], theoretical perspectives [ 25 , 28 , 29 ], or just a press release report [ 21 , 23 , 24 ]. While some of the studies focused specifically on ACB population [ 23 , 24 , 27 ], the majority focused on minorities and marginalized communities [ 21 , 22 , 25 , 26 , 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…From all these studies, only one has collected original data involving 1478 adults [ 26 ]. The rest of the studies were comments [ 27 ], theoretical perspectives [ 25 , 28 , 29 ], or just a press release report [ 21 , 23 , 24 ]. While some of the studies focused specifically on ACB population [ 23 , 24 , 27 ], the majority focused on minorities and marginalized communities [ 21 , 22 , 25 , 26 , 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Social restrictions are initiated for all citizens, including students who are strictly prohibited from leaving home except for the limited purposes permitted by the Orders. Glover et al [1], Yousefpour et al [2] and Nicola et al [3] review each of the policies taken aiming to put a halt to Covid-19, despite the fact that Viner et al [4] found the closure of school services had no major impact, only preventing 2-4% of the total of deaths, far less than other social distance interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, these recommendations can be implemented most effectively by privileged individuals—those with secure housing, monetary resources, tangible social support, access to medical care, power to self-advocate to receive a test in contexts with limited tests, and white-collar professions that easily transition to remote work for physical distancing ( Valentino-DeVries et al, 2020 ). A recent analysis of COVID-19 policy interventions indicates the extent of their potential inequitable impacts on some population groups ( Glover et al, 2020 ). In addition, the recommendations may not be as applicable to low and middle income countries (LMIC) as to high income countries; context matters ( Cash and Patel, 2020 ; Kelley et al, 2020 ).…”
mentioning
confidence: 99%
“…COVID19 is a like a ‘canary in the coal mine’, highlighting conditions that make people differentially susceptible to all diseases ( Navarro and Shi, 2001 ; Sharma, 2017 ). In our prevention and mitigation responses, we must prioritize the most socially vulnerable to begin to reverse disparities and health inequities ( Glover et al, 2020 ; Berger et al, 2020 ; Gostin et al, 2020 ). After all, public health has two moral aims, one to improve population health and second to reduce health inequities ( Powers and Faden, 2013 ).…”
mentioning
confidence: 99%